DEVELOPMENT OF A MOBILE WEB-BASED INVENTORY MANAGEMENT INFORMATION SYSTEM AT GUNUNG TERANG SPARE PARTS STORE - Maulana, Muhammad; Yansahrita, Yansahrita (JMBI (Journal of Marketing and Business Intelligence), 2025)
The rapid development of information technology has significantly influenced business operations, particularly in inventory management within retail sectors. This study aims to develop a web mobile-based inventory management information system for Gunung Terang Sparepart Store to address issues related to manual recording, which often leads to data inaccuracies and delays in reporting. The system is designed to manage incoming and outgoing goods, monitor stock levels in real-time, and generate financial reports efficiently. The development process utilizes a web-based approach supported by a modern framework and MySQL database to ensure data integrity and system scalability. Black Box Testing is applied to evaluate the system’s functionality by validating input and output without examining internal code structures. The results indicate that the system improves accuracy in stock management, accelerates transaction processing, and enhances decision-making through real-time reporting. Furthermore, the integration of mobile accessibility allows users to monitor operations anytime and anywhere, increasing flexibility and productivity. This research contributes to the implementation of digital solutions in small and medium enterprises, particularly in optimizing inventory control and financial management processes in retail environments.